Inovasi Pembelajaran PAI Abad 21 - Okita Maya Asiyah (Prodi Pendidikan Agama Islam IAI Al-Qodiri Jember, 2022)
PAI learning is currently considered to be monotonous in delivery so as to cause boredom in learners. This needs innovation in PAI learning, so that PAI learning can be received with pleasure by learners. This research aims to find out: 1) Describe the meaning of PAI learning. 2) Describes 21st century learning. 3) Analysis of PAI learning innovation of the 21st century. This research is a type of library research with a descriptive approach to analysis (descriptive of analyze research). The results of this study are: 1) Change the orientation of education. During this time educational assessment only focuses on cognitive, but must also focus on the psychomotor and affective realm. 2) It is necessary to develop Islamic Education learning that is able to connect with the education system comprehensively..